Antioxidant enzymes activity, GSH and MDA level in eggs from heritage breeds - Muchacka , Renata; Sosnówka-Czajka, Ewa; Skomorucha , Iwona; Kapusta , Edyta; Greń , Agnieszka; Goc , Zofia (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2018)
The objective of the study was to determine the activity of antioxidant enzymes and the level of GSH and MDA in yolk and albumen of hen’s eggs. The experiment was carried out with 99 hens of three heritage breeds (‘Greenleg Partridge’ - group I, ‘Sussex’ - group II, ‘Rhode Island Red’ - group III). Layers were reared in the litter system and had outdoor access. Birds were fed ad libitum standard diets based on concentrates for laying hens and had free access to water throughout the experiment. All the groups were managed under uniform environmental (air humidity and temperature, lighting programme) and feeding conditions. At 48 weeks of age, 6 eggs from each group were collected. In the samples of egg yolks and albumens the concentration of GSH and MDA, and activity of SOD, GPx and CAT were estimated. The results were statistically analysed by one-way analysis of variance and significant differences were estimated with Duncan’s multiple range test. The highest activity of SOD, the highest level of GSH and the lowest level of MDA were characterised by eggs from ‘Sussex’ hens, which may indicate their best quality. Based on the obtained results, it can be concluded that the activity of antioxidant enzymes (mainly SOD) and the levels of GSH and MDA which occur in eggs may depend on the breed of hens.